Optimization of ionic liquid assisted sugar conversion and nanofiltration membrane separation for 5-hydroxymethylfurfural - Sarwono, A. (2019)
This paper provides complete loop of ionic liquid (IL) assisted glucose conversion to 5-hydroxymethylfurfural (HMF), nanofiltration membrane (NF) based separation and recyclability. The optimum HMF yield of 65.6 was obtained with 8 wt. catalyst loading at 125 Â°C reaction temperature in 120 min reaction time. Ea for conversion was found to be 120 kJ/mol. NF was adopted first time to separate IL and HMF. The percentage of recovered HMF using NF for 1st, 2nd and 3rd batches are 94.87, 84.35 and 71.65 respectively. The structures of regenerated IL and HMF, obtained from NF and liquidâliquid extraction, were confirmed by NMR. Â© 2018 The Korean Society of Industrial and Engineering Chemistry